Planning for hospitable public spaces and the changing city: A content analysis of the city of Sunderland Unitary Development Plan. Issue 3 (1st September 2019) - Morton, Ian Joseph; Johnson, James
A plethora of new public spaces have been developed in central areas of many British cities. There is evidence of the emergence of new tourism and hospitality developments (particularly hotels) close to public spaces, which could influence how the spaces are used. Whilst an ongoing discussion of the hospitable city is prevalent within the literature, no study to date has focused specifically on the symbiosis of tourism, hospitality and public space in planning policy documents. To gain a better understanding of how cities plan for a productive relationship between tourism and hospitality and public space and hotel development this article presents a content analysis of the city of Sunderland's Unitary Development Plan entitled UDP Alteration No. 2 (Central Sunderland) Adopted Policies, this being the central legal urban planning policy document that guides change in the city. The results of the content analysis suggest three central themes of prestige, variety and vibrancy.